Not So Grim: Liz Lochhead’s Subversion of Patriarchy in The Grimm Sisters - Merve Sarı (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Although originally folk and fairy tales belonged to female story-tellers who had composed these tales, their hold on the stories was gradually lost due to the rising interest of writers like Perrault and the Grimms in these tales. While putting these narratives down, male authors never simply wrote these tales down as they heard them but adapted them in a certain way to promote their patriarchal ideologies through these texts. In the last quarter of the twentieth century, however, postmodern writers, relying on intertextuality and the fantastic challenged the ancient lore, subsequently re-writing and questioning the reliability of these so-called “original” tales. Particularly female authors writing in the postmodern tradition challenged the central by replacing it with the peripheral, through their employment of such techniques as irony, satire, parody and pastiche. Among these writers, Scottish poetess Liz Lochhead stands out with her attempt to recover the “absent” voices in fairy tales. Re-writing the fairy tales of the Grimm Brothers from a female perspective in The Grimm Sisters (1981), Lochhead via her poems subverts the role of the traditionally silent part attributed to women, while voicing the concerns of women as story-tellers, mothers, wives, daughters, sisters, step-mothers, hags and the “other” women. In this regard, the aim of this article is to discuss the role of postmodern techniques and the fantastic in enabling Lochhead to subvert the conventional roles ascribed to women in her The Grimm Sisters and re-write the contemporary feminine experience as it is perceived and experienced by women per se.